Development of Creative Skills of Students in Modern Educational Conditions - Abdullaeva Dilnoza Narzullaevna; Allakhova Gulshikhra Yerejepbaevna (Zien Journals, 2024)
In the conditions of modern education, classes organized on the basis of innovative technologies in academic subjects encourage students to think, to think, to think logically, to put forward original ideas on the subject being studied. In this article, the world educational experience of developing the creative abilities of students of general education schools, the researches conducted in this regard, as well as the issues of effective organization of modern education and the development of creative qualities in students are covered
Keywords: modern education; educational efficiency; creative qualities